Moored observations of synoptic and seasonal variability in the East Greenland Coastal Current. Issue 12 (23rd December 2014) - Harden, B. E.; Straneo, F.; Sutherland, D. A.
Abstract We present a year‐round assessment of the hydrographic variability within the East Greenland Coastal Current on the Greenland shelf from five synoptic crossings and 4 years of moored hydrographic data. From the five synoptic sections the current is observed as a robust, surface intensified flow with a total volume transport of 0.66 ± 0.18 Sv and a freshwater transport of 42 ± 12 mSv. The moorings showed heretofore unobserved variability in the abundance of Polar and Atlantic water masses in the current on synoptic scales. This is exhibited as large vertical displacement of isotherms (often greater than 100 m). Seasonally, the current is hemmed into the coast during the fall by a full depth Atlantic Water layer that has penetrated onto the inner shelf. The Polar Water layer in the current then thickens through the winter and spring seasons increasing the freshwater content in the current; the timing implies that this is probably driven by the seasonally varying export of freshwater from the Arctic and not the local runoff from Greenland. The measured synoptic variability is enhanced during the winter and spring period due to a lower halocline and a concurrent enhancement in the along‐coast wind speed. The local winds force much of the high‐frequency variability in a manner consistent with downwelling, but variability distinct from downwelling is also visible.